Characterization on the cardiac function of hypothermic dogs from cold water immersion - Chengxiang Lei; Jiangzhou Ding; Gaochao Si; Hui Zhang; Wei Zhu; Zhiyong Peng; Wei Wang (Актуальні проблеми транспортної медицини, 2011)
OBJECT To clarify the effects of cold water immersion on the canine cardiac function and how to prevent the immersed hypothermic ventricular fibrillation. METHODS 7 normal male dogs, which were randomly divided into two groups, the experimental (3, each with 2.5mg/kg nimodipine) and the control (4), were immersed in cold water at 6 ± 1!. The polygraph system was used to record the cardiac function and the transmission electron microscope was involved to study the ultrastructure changes of myocardium. The activity levels of Na⁺:K⁺:ATPase and Ca²⁺:ATPase were measured by means of Elisa. RESULTS As the canine core temperature going down, it was noted that the left ventricular pressure peak value (LVSP), and the isovolumetric contraction phase maximal ascending/descending velocity ( ± dP/dtmax) decreased evidently, with a prolonged Q:T duration, and that hypothermic J waves were found subsequently. The activities of Na⁺:K⁺:ATPase and Ca²⁺ATPase were both inhibited. There came rapid ventricular arrhythmia with the control dogs, while not with the experimental. CONCLUSIONS The hypothermia would result in the weakening of canine cardiac function, moreover, the appearance of J wave might be followed by the occurrence of hypothermic ventricular fibrillation. The results also suggested that nimodipine might have a potential to prevent immersed hypothermic ventricular fibrillation.